A critical geography approach to land and water use in the tourism economy in Los Cabos, Baja California Sur, Mexico. Issue 2 (3rd May 2020) - Graciano, Juan Carlos; Ángeles, Manuel; Gámez, Alba E.
ABSTRACT: This paper offers a critical assessment of how tourism development in the municipality of Los Cabos, Baja California Sur affects land and water use. Los Cabos is a seaside tourism Mecca located at the southern tip of the Baja California peninsula, in Mexico's northwest. There, subsidised profits and a process of dispossession in the tourism sector have to do mainly with land and water appropriation in the form of restrictions to beach access by the local population, urban segregation and, in an arid region, privileging water provision for the tourism industry over the needs of the population. In order to sustain these claims, we map water and land use for tourism in Cabo San Lucas. We also analyse the expansion of the Los Cabos type of tourism to the small town of La Ribera, in the East Cape-Cabo Pulmo area, where marinas and high scale housing for residential tourism sprout along the coast. We argue that the seemingly ever-growing presence of tourism in the region carries with it an urgent call for the reappraisal of current approaches to land and water use, if local resources are to deliver quality of life for the population, and not only economic profitability for (mostly) foreign capital. Analytically, we address these issues by unpacking David Harvey's concept of accumulation by dispossession, which – we argue – is for our purposes a broader tent than the (mostly Latin American) theorisations on extractivism, as we explain later in the relevant section of the paper.